Exploring community newspapers and brand building in the digital age - Nobin, Christine Elise (The IIE, 2016)
The purpose of this paper was to establish the purpose of community newspapers and how this communication platform can be explored within a brand building and digital paradigm. To do this, research into community news, media convergence, digitisation, brand purpose was conducted. This was done with the aim to gain insights that prompted a deeper look into the research topic via a qualitative approach using in-depth interviews and a focus group. The use of three core questions guided the research process, with the ultimate goal to establish the purpose of community newspapers; how this should be communicated in a digital age; and whether print and digital communication platforms are competitors or companions. The research title, Exploring Community Newspapers and Brand Building in the Digital Age, therefore links to the interest in the communications industry and furthermore to how a newspaper brand can communicate with its audience in the age of multiplatform delivery. Findings show that despite the shift from print to digital, newsrooms are finding the need to balance both communication platforms. This linked to the insight that the increase of citizen journalists created an opportunity for news brands to bring traffic to their websites by including the public in the reporting of news. News platforms needed to understand the importance of brand building and brand purpose to ensure the longevity of both its print and digital news forums.
Thesis
Keywords: Community newspapers; Brand building; Digital paradigm; Brand communication; Print